Ethics and Morality in Islam and Hinduism - Abbas, Sarim; Jalaluddin, Mohammad (INSANCITA, 2016)
ABSTRACT: Hinduism and Islam are the two largest religions of the world. Hinduism is the socio-religious way of life from the Hindu people in the Indian subcontinent. Islam is aÂ strictlyÂ monotheistic religion in which the supreme deity isÂ Allah,Â and Prophet Mohammad SAW (Salallahu âAlaihi Wassalam or Peace Be Upon Him) is the last Prophet. The primary Islamic scripture is theÂ Al-Qurâan, Allahâs book; andÂ Al-Hadith, which are traditional records of theÂ sayings and acts of Prophet Muhammad SAW. The scriptures of Hinduism are theÂ ShrutisÂ (the fourÂ Vedas, which comprise the original Vedic Hymns, or Samhita, and three tiers of commentaries upon the Samhita, namely the Brahmanas, Aranyakas, and Upanishads); these are considered authentic, authoritative divine revelation. Furthermore, Hinduism is also based on the Smritis,Â including the Ramayana and the Bhagavad Gita,Â which are considered to be of secondary authority and of human creation. Both religions, Hindu and Islam, give importance to ethics and morality. We focus our discussion in this article on ethical and moral values in Islam and Hinduism. Islamic moral is a combination of genuine acts of love and justice on the one hand, and legalistic performances on the other. Muhammad is pictured in the Al-Qurâan as a loving person, helping the poor, and slow to take revenge. Meanwhile, on Hinduism, because of the vast number of reincarnations of any given individual, it recognizes that most peopleâs lack of spiritual development; its means they must lead normal lives that can grow closer to the ideal of full renunciation of the personality.KEY WORD: Islam and Hinduism, socio-religious way of life, monotheistic religion, ethics and morality, Al-Quâan and Al-Hadith, four Vedas, straight path, reincarnation, and good personality.ABSTRAKSI: âEtika dan Moralitas dalam Agama Islam dan Hinduâ. Hindu dan Islam adalah dua agama terbesar di dunia. Hindu adalah cara hidup sosial-keagamaan dari masyarakat Hindu di anak benua India. Islam adalah agama monotheis yang tegas dimana Tuhan tertinggi adalah Allah, dan Nabi Muhammad SAW (Salallahu âAlaihi Wassalam) adalah Nabi terakhir. Kitab utama agama Islam adalah Al-Qurâan, kitab Allah; dan Al-Hadith, yang mencatat tradisi dari ucapan dan tindakan Nabi Muhammad SAW. Kitab suci agama Hindu adalah Shrutis (empat Veda, yang terdiri dari Veda Nyanyian Rohani asli, atau Samhita, dan tiga tingkatan komentar pada Samhita, yaitu Brahmana, Aranyaka, dan Upanishad); ini dianggap otentik, wahyu berotoritas ilahiyah. Selanjutnya, Hindu juga berdasarkan pada Smritis, termasuk Ramayana dan Bhagavad Gita, yang dianggap sumber otoritas sekunder dan ciptaan manusia. Kedua agama, Hindu dan Islam, menekankan pentingnya etika dan moralitas. Kami memfokuskan diri dalam pembahasan artikel ini mengenai nilai-nilai etika dan moral dalam agama Islam dan Hindu. Moral Islam adalah kombinasi antara tindakan cinta sejati dengan keadilan di satu sisi, serta petunjuk legalistik di sisi lain. Muhammad digambarkan dalam Al-Qurâan sebagai manusia penuh cinta-kasih, menyayangi orang miskin, dan bersikap memaafkan daripada membalas dendam. Sementara itu, pada agama Hindu, karena banyaknya reinkarnasi bagi setiap individu bermakna bahwa kebanyakan orang kurang dalam pengembangan spiritual; artinya mereka harus menjalani kehidupan normal yang dapat tumbuh dan bersatu kembali dengan kepribadian utuh yang ideal.KATA KUNCI: Islam dan Hinduisme, cara hidup sosial-keagamaan, agama tauhid, etika dan moralitas, Al-Qurâan dan Al-Hadith, empat kitab Veda, jalan lurus, reinkarnasi, dan kepribadian yang baik.Â Â About the Authors: Sarim AbbasÂ and Mohammad Jalaluddin are Ph.D. Students at the Department of Philosophy and English AMU (Aligarh Muslim University) in Aligarh 202002, Uttar Pradesh, India. For academic interests, the authors are able to be contacted via their e-mails at: sarim007@gmail.com and jalalamu@gmail.comHow to cite this article? Abbas, Sarim & Mohammad Jalaluddin. (2016). âEthics and Morality in Islam and Hinduismâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Vol.1(1), February, pp.37-42. Bandung, Indonesia: Minda Masagi Press, ISSN 2443-1776.Chronicle of the article: Accepted (July 6, 2015); Revised (October 9, 2015); and Published (February 5, 2016).